Using Restricted Least Squares Method to Estimate and Analyze the Cobb-Douglas Production Function with Application - Gorgess, H. M.; Abdul Naby, A. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, the restricted least squares method is employed to estimate the parameters of the Cobb-Douglas production function and then analyze and interprete the results obtained. A practical application is performed on the state company for leather industries in Iraq for the period (1990-2010). The statistical program SPSS is used to perform the required calculations.